Kebijakan dan Kepemimpinan Transformasional di SMP dalam Meningkatkan Mutu Pendidikan di Kota Bima - Fathiha, Nuril; Achadi, Muh. Wasith (Lembaga Yasin AlSys, 2023)
This study aims to explain policies and transformational leadership in improving the quality of education. The location is in Bima City. The discussion in this paper covers the notion of transformational leadership, the characteristics of transformational leadership, and the implications of transformational leadership and policies in improving the quality of education. This research uses qualitative research methods (qualitative research). Types of library research (library research). Using documentation study techniques (documentations study). Data collection was carried out through a systematic search of scientific literature on articles, books and documents that discussed significantly and had a connection with the research theme. The results of this study indicate that there is such a large contribution of transformational leadership in the development of better collar education. Through this article, it is hoped that it can provide benefits for readers, especially for the world of education to move towards a better direction, by implementing transformative leadership in its leadership. As a first step towards change in the world of education.